Specific genomic cues regulate Cajal body assembly. Issue 6 (3rd June 2017) - Sawyer, Iain A.; Hager, Gordon L.; Dundr, Miroslav
ABSTRACT: The assembly of specialized sub-nuclear microenvironments known as nuclear bodies (NBs) is important for promoting efficient nuclear function. In particular, the Cajal body (CB), a prominent NB that facilitates spliceosomal snRNP biogenesis, assembles in response to genomic cues. Here, we detail the factors that regulate CB assembly and structural maintenance. These include the importance of transcription at nucleating gene loci, the grouping of these genes on human chromosomes 1, 6 and 17, as well as cell cycle and biochemical regulation of CB protein function. We also speculate on the correlation between CB formation and RNA splicing levels in neurons and cancer. The timing and location of these specific molecular events is critical to CB assembly and its contribution to genome function. However, further work is required to explore the emerging biophysical characteristics of CB assembly and the impact upon subsequent genome reorganization.